Edukasi Sadar Bencana Melalui Transfer Knowledge Sebagai Upaya Peningkatan Pengetahuan Masyarakat Terhadap Mitigasi Bencana - Fajri Valentino; Rahmadani Yusran; Allif Khairul Diffa; Stefany Faulina; Handayani Nurqoriah (BADAN PENERBIT STIEPARI PRESS, 2023)
Natural disasters from year to year become records as well as data on how natural disasters are very detrimental to the survival of mankind as a history, therefore the need for disaster preparedness as an anticipation in disaster management. The research approach used is a descriptive qualitative approach which aims to analyze and describe disasters and disaster mitigation in an area. This study is motivated by the fact that in Nagari Pariangan there is a low level of public knowledge about disaster mitigation. In addition, there has been no presentation of material on mitigation of volcanic eruptions and landslides in disaster-prone areas, so the role of the government and students is needed to transfer material knowledge about mitigation to the community. This study aims to develop volcano and landslide disaster mitigation efforts for the people of Nagari Pariangan, Pariangan District, Pariangan Regency in the form of disaster mitigation education and awareness activities.